Gêneros no contexto brasileiro: questões meta(teóricas) e conceituais, de Benedito Gomes Bezerra - Paiva, Francisco Jeimes de Oliveira; Lima, Ana Maria Pereira (Revista Letra Capital, 2017)
BEZERRA, Benedito Gomes. Gêneros no contexto brasileiro: questões [meta]teóricas e conceituais. São Paulo: Parábola Editorial, 2017. 136p